Methodologies to evaluate the quality of pedestrian infrastructure on the University campus: Systematic Review - Pires, Bruna Cristina; Magagnin, Renata Cardoso; Fontes, Maria Solange Gurgel de Castro; Azambuja, Maximiliano dos Anjos (Revista Nacional de Gerenciamento de Cidades, 2022)
Walking is understood as a sustainable and economical means of transport, it promotes benefits such as improving people's health, but this option is chosen especially when adequate conditions are offered. As it contributes to the adoption of a sustainable urban mobility policy, walking should be encouraged in internal displacements carried out by users of higher education institutions. To support the analysis of mobility in this type of institution, this paper sought to identify the main methods and techniques that can be used to evaluate the quality of walking spaces, internal and external, to University campuses, through a systematic review of literature. For this, Scopus, MDPI, ScienceDirect and Sage Journals platforms were adopted to screen articles published between 2005 and 2021, with the following keywords “walkability, campuses, university” and “pedestrian, “campuses, university”. The analysis of 26 papers, which were part of the sample size, made it possible to identify: i) objective, ii) methodology and iii) technique used among the researchers, and showed that predominantly the research carried out in these environments incorporates not only the spaces within the campus, but its surroundings, or users' access to the campus. Thus, several aspects associated with walkability are evaluated, such as the existing infrastructure itself, the most used mode of transport in displacements within the campus, in addition to some scenario in a certain route carried out by the user.